Exchange rate volatility and its impact on Nigeria's exports: An Autogressive Distributed Lag (ARDL) Analysis - Okogor, Chuks; Orubu , Christopher O.; Ezi, Chukwugoziem T. (Acta Universitatis Danubius. Œconomica, 2023)
Nigeria's trade volume and value with other countries have increased significantly. According to the Economic Complexity Index (ECI, 2021), Nigeria is ranked the 52nd largest economy in terms of total exports ($57.7 billion) and the 30th largest economy in terms of GDP ($440.83 billion in current US dollars). Nigeria's top five export destinations are Spain, the United States, France, and China. Using the standard demand function, this study examined the effect of exchange rate volatility on Nigeria's exports to the top five export destinations for the period 1995–2020 in an autoregressive distributed lag (ARDL) mode. The empirical results show that exchange rate volatility, gross domestic product, and population are strong determinants of real exports in Nigeria, both in the short and long run. The results further show that the depreciation of the naira tends to increase exports for France and Spain in the short run and for France, India, and Spain in the long run. While it reduces exports for China and the USA in the short run, its impact is insignificant for India in the long run. Relative prices had an adverse effect on exports in most countries, both in the short and long run. Among others, this study recommends that the standard organization of Nigeria, in conjunction with the export promotion council, should synergize and set up a standard itch-free verification system that will ensure that Nigerian goods meant for export are of international quality. More so, monetary authorities should improve the availability of hedging instruments and promote the use of hedging among exporters to support them in coping with exchange-rate uncertainty. Lastly, there is a need for an appropriate pricing template for categories of export products to avoid the deleterious effects of relative prices. This study also recommends that future studies can investigate the asymmetric effects of exchange rate volatility on exports.